Gendered Marketing - Maclaran, Pauline; Maclaran, Pauline; Chatzidakis (Cheltenham, UK Edward Elgar Publishing, 2023)
"Performing an in-depth exploration of the gendered nature of marketing theory and practice, this timely book unpacks the many ideological assumptions embedded in marketing thought and action. Drawing on past and present scholarship at the intersection between marketing and feminism, Pauline Maclaran and Andreas Chatzidakis highlight the gendered silences in the history of marketing. By referencing core bodies of feminist theory and engaging with interdisciplinary perspectives on feminism and marketing, they illustrate a comprehensive understanding of the subtleties at work in the gendering of marketing. Structured around five key areas, the book examines the history of marketing thought, communications, product design and branding, marketing's free externalities, and the marketing organisation. Identifying the biases, misconceptions and prejudices perpetuated by gendered marketing, it concludes by questioning if and how marketing can be de-gendered, in order to empower and transform consumers. Tracking the evolution of feminist thought and its critique of market-related structures and activities, this book will prove invaluable to students and scholars of marketing, media studies, sociology and gender studies. With insights into industry practices, it will also prove a vital reference guide to practitioners and policymakers working in advertising, marketing and the media who are concerned with gender and feminism"
Keywords: Marketing--Social aspects; Marketing--Sex differences; Feminist theory